Parametric Sensitivity Analysis of Factors Affecting Sound Transmission Loss of Multi-Layered Building Elements Using Taguchi Method - GARG, Naveen; KUMAR, Anil; MAJI, Sagar (Archives of Acoustics, 2014)
The paper presents application of Taguchi method in optimizing the sound transmission loss through sandwich gypsum constructions and those comprising of masonry concrete blocks and gypsum boards in order to investigate the relative influence of the various parameters affecting the sound transmission loss. The application of Taguchi method for optimizing sound transmission loss has been rarely reported. The present work uses the results analytically predicted on “Insul” software for various sandwich material configurations as desired by each experimental run in an $L_8$ orthogonal array. The relative importance of the parameters on single-number rating, $R_w$ ($C$, $C_{tr}$) is evaluated in terms of percentage contribution using Analysis of Variance ($ANOVA$). The $ANOVA$ method reveals that type of studs, steel stud frame and number of gypsum layers attached are the key factors controlling the sound transmission loss characteristics of sandwich multi-layered constructions.